(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Modern hockey requires athletes to be able to apply a wide range of technical and tactical techniques in training and competition conditions, due to the availability of knowledge about the methods of conducting sports. The setting of situational tasks in the process of tactical and technical training of athletes allows for a more objective consideration of game activity, extrapolating the structure of actions to the structure of the game. In addition, the problem of the differentiation of the content of game activity, which is reflected in textbooks on sports games by the sections on technique and tactics of the game, is solved. The purpose of the study is to theoretically substantiate and experimentally verify the effectiveness of the method of teaching individual tactical and technical actions of 10-11-year-old hockey players based on the construction of situational tasks. Research methods. Theoretical research methods were used in the work: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodical literature, pedagogical testing, pedagogical experiment, methods of mathematical statistics. Work results. After the end of the formative stage of the pedagogical research, the average indicator of dribbling the ball, going around the uprights, hitting the goal of the hockey players of the experimental group was better compared to the control group by 2.41 s (р<0.05), dribbling, passing the ball into the goal – by 6.60 s (р<0.05), long throw of the ball with a stick – by 2.98 m (р<0.05), shuttle run 6x9 m – by 0.95 s (р<0, 05), long jump – by 23.41 cm (p<0.05). Conclusions. Empirically, it was proved that the application of the method of improving the individual tactical and technical actions of hockey players aged 10–11 years based on the construction of situational tasks contributed to a significant increase in the technical readiness of the hockey players of the experimental group